Avaliação e monitoria da função vestibular por meio do teste do impulso cefálico por vídeo em pacientes com disfunção vestibular - Aguiar, Maria Carolaine Ferreira (2022)
Introduction: The video head impulse test (vHIT) objective assessment of the vestibulo-ocular reflex (VOR) at high frequency. Objective: (1) To characterize the effect of vestibular rehabilitation (VR) on VOR gain, saccades, body balance and quality of life in three patients with peripheral vestibular hypofunction. (2) To compare the values of VOR gain, asymmetry between the semicircular canals (SCCs) and saccadic parameters in patients with Méniere's Disease (MD) and vestibular migraine (VM). Method: Study approved by the Research Ethics Committee, opinion nº 4.462.519. Dissertation structured in two articles. (1) Report of three cases submitted to VR and monitored by vHIT. (2) A cross-sectional and retrospective study, medical records of individuals diagnosed with MD and VM who underwent vHIT were selected. Results: (1) An increase in VOR gain was observed, consistent with normality standards and, extinction or reduction of saccades, in the three cases. (2) The sample consisted of 33 individuals, 18 from group 1 (G1), with VM, and 15 from group 2 (G2), with MD. In vHIT, there was a predominance of normality in the gain of VOR for G1 and vestibular hypofunction for G2. There was no difference between the average gain, per SCCs, nor in the right and left SCCs, between G1 and G2. There was a difference in asymmetry between the posterior SCCs (p=0.042). Conclusion: In this study, the vHIT was considered a useful instrument for monitoring vestibular function after VR (1), allowing us to identify the predominance of vestibular hypofunction in the DM group and normal results in the MV group, but with no statistical difference (2).